Evaluation of the clinical value of automatic online dose restoration for adaptive proton therapy of head and neck cancer. (May 2022) - Borderías-Villarroel, Elena; Taasti, Vicki; Van Elmpt, Wouter; Teruel-Rivas, S.; Geets, X.; Sterpin, E.
Highlights: An online adaptive strategy was compared to not-adaptation of robust clinical plans and offline adaptation. Not-adapted robustly optimized plans achieved adequate target coverage in up to only 26% of repeated-CTs. Dose restoration yielded adequate target coverage in 52% of repeated-CTs. Dose restoration reduced the dose to most organs-at-risk compared to not-adaptation of robust clinical plans. Full offline adaptation was still required in 48% of repeated-CTs. Abstract: Introduction: Intensity modulated proton therapy (IMPT) is highly sensitive to anatomical variations which can cause inadequate target coverage during treatment. This study compares not-adapted (NA) robust plans to two adaptive IMPT methods - a fully-offline adaptive (FOA) and a simplified automatic online adaptive strategy (dose restoration (DR)) to determine the benefit of DR, in head and neck cancer (HNC). Material/methods: Robustly optimized clinical IMPT doses in planning-CTs (pCTs) were available for a cohort of 10 HNC patients. During robust re-optimization, DR used isodose contours, generated from the clinical dose on pCTs, and patient specific objectives to reproduce the clinical dose in every repeated-CT(rCT). For each rCT(n = 50), NA, DR and FOA plans were robustly evaluated. Results: An improvement in DVH-metrics and robustness was seen for DR and FOA plans compared to NA plans. For NA plans, 74%(37/50) of rCTs did not fulfill the CTV coverage criteria (D98%>95%Dprescription). DR improved target coverage, target homogeneity and variability on critical risk organs such as the spinal cord. After DR, 52%(26/50) of rCTs met all clinical goals. Because of large anatomical changes and/or inaccurate patient repositioning, 48%(24/50) of rCTs still needed full offline adaptation to ensure an optimal treatment since dose restoration was not able to re-establish the initial plan quality. Conclusion: Robust optimization together with fully-automatized DR avoided offline adaptation in 52% of the cases. Implementation of dose restoration in clinical routine could ensure treatment plan optimality while saving valuable human and material resources to radiotherapy departments.